MIGRAÇÃO E REFUGIADOS UM OLHAR PARA A EDUCAÇÃO INCLUSIVA NO SÉCULO XXI - Silva, Vinícius Alves da (2019)
On the subject of migration, the dissertation presents here comes the arrival and stay of Syrian refugees in Brazil, with a focus on the city of Florianópolis, Santa Catarina, and inclusion in the educational context against the differences cultural and linguistic. Aims to investigate and discuss the way they are welcomed in educational sphere by means of educational laws, as well as the challenges that these students are facing the difficulties idiomatic and cultural differences. The theoretical analysis is based on literature search that explained the conceptual understandings linked to the concept of refugee, the history of Syria, the question of inclusion/integration of refugees in the school context and focuses on the relations between identities, cultural diversity, multiculturalism, interculturalism and integration of cultures. The documentary analysis researched about the relevant legal systems to the refuge and in the field of education, with a focus on guidelines and foundations of education, national curriculum parameters and in the Curricular Proposal. The final axis of analysis was run through field research, with interviews and participant observation in two schools in the State schools in the city of Florianópolis, noting the relationship between Syrian refugees and students the school community and the educational Dynamics to promote integration. The results show, from the analysis of the laws governing education, although these laws predict the respect for diversity and value for the inclusion in the school environment, do not specify the issue of student refugee, not offering any kind of support to This reception, as Portuguese language learning or psychological. From the field study, the conclusion was that the institutions seek inclusive measures and develop projects to promote the integration of foreign exchange student, returning the strategies for the implementation of the language barrier and the teaching of plurality cultural. Individual school strategies demonstrate the importance of minor education when there are mobilizing at school and when this part of the teachers of the school itself.